A new species of Simaba sect. Grandiflorae (Simaroubaceae) from Jalapão region, Tocantins, Brazil - Devecchi, Marcelo Ferenando; Pirani, José Rubens (Phytotaxa, 2015)
Simaba tocantina, a new species of Simaroubaceae, is described and illustrated. It belongs to Simaba sect. Grandiflorae since its flowers reach 21–25 mm long and its staminal appendages are covered by intertwined trichomes forming a pseudotube around the gynoecium. Its differences from the related species in the section are pointed out herein, including a key to the five species of the group. As other cerrado members in the genus, the new species is a shrub with a thickened underground system, from which a few aerial branches develop, as well as a long, erect, showy inflorescence. It is known only by a few records from the cerrado of the Jalapão State Park in Tocantins, Brazilian Central Plateau, and its conservation status is assessed.